STRENGTHENING EFL PRE-SERVICE TEACHER’S PEDAGOGIC COMPETENCE THROUGH EXTENSIVE READING - Novi Rahmania Aquariza; Syafiul Anam (E-LINK JOURNAL, 2019)
In this article a brief explanation of what Extensive Reading is presented. The article starts by presenting the common idea of what Extensive Reading is. Then the possible advantages and obstacles of it are also presented as well as the previous study related. Then, the origin of pedagogic competence stated in line with the implementation of how to apply the Extensive Reading in the teaching and learning process are also detailed in the end of this article.  Keywords: Extensive Reading, Pedagogic Competence